2020
DOI: 10.1017/s0022377820000938
|View full text |Cite
|
Sign up to set email alerts
|

Zonally dominated dynamics and Dimits threshold in curvature-driven ITG turbulence

Abstract: The saturated state of turbulence driven by the ion-temperature-gradient instability is investigated using a two-dimensional long-wavelength fluid model that describes the perturbed electrostatic potential and perturbed ion temperature in a magnetic field with constant curvature (a $Z$ -pinch) and an equilibrium temperature gradient. Numerical simulations reveal a well-defined transition between a finite-amplitude saturated state dominated by strong zonal-flow and zonal temperature p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(126 citation statements)
references
References 81 publications
13
111
1
Order By: Relevance
“…On the contrary, for minima of the flow, , the phase velocity has a saddle point and turbulent structures are expelled. This asymmetry has been observed in numerical simulations for gyro-kinetic toroidal systems (McMillan et al 2011; Dif-Pradalier et al 2015; Zhu et al 2018 b ; Gillot 2020; Ivanov et al 2020). The same generic mechanism exists for a stationary zonal flow (Zhu, Zhou & Dodin 2020): the stability of the zonal flow pattern depends on the sign of the curvature.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…On the contrary, for minima of the flow, , the phase velocity has a saddle point and turbulent structures are expelled. This asymmetry has been observed in numerical simulations for gyro-kinetic toroidal systems (McMillan et al 2011; Dif-Pradalier et al 2015; Zhu et al 2018 b ; Gillot 2020; Ivanov et al 2020). The same generic mechanism exists for a stationary zonal flow (Zhu, Zhou & Dodin 2020): the stability of the zonal flow pattern depends on the sign of the curvature.…”
Section: Discussionmentioning
confidence: 61%
“…The scale separation allows the treatment of the waves as point particles, neglecting their finite correlation length, and their response to profile evolution is instantaneous. However, the radial scale separation may only be marginal, because of the radial pattern of zonal flow staircases (Dif-Pradalier et al 2015; Ivanov et al 2020). The case of non-ideal waves is plagued by numerous technical and fundamental difficulties that we can avoid here by restricting ourselves to the ideal case (Brillouin 1960).…”
Section: Derivation Of the Wave-kinetic Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zonal flows play a major role in the dynamics of "E × B" staircases, which are self-organised turbulent states observed in a number of gyrokinetic simulations [16,17,18,19,20,21]. Similar patterns were observed in simulations of a reduced 2D model of interchange turbulence [22] and also 2D ion temperature gradient (ITG) turbulence [23]. Some experimental observations were found consistent with a staircase phenomenology [24,25,26].…”
Section: Introductionmentioning
confidence: 68%
“…Understanding of the Dimits shift is already complicated when we study the modified Hasegawa-Wakatani model in Zhu et al (2020), when we observed the presence of avalanche-like structures, which are not supported by the mTHE. Furthermore, the recent paper by Ivanov et al (2020) shows that avalanches themselves can become intricate when additional physics due to finite ion temperature is taken into account. This complicates the problem even further, and more work remains to be done to understand the Dimits shift in the general case.…”
Section: Introductionmentioning
confidence: 99%